Enlargement of Dorello's Canal as a Novel Radiographic Marker of Idiopathic Intracranial Hypertension - Eggerstedt, Michael; Dua, Sumeet G.; Varelas, Antonios N.; Bhabad, Sudeep H.; Batra, Pete S.; Tajudeen, Bobby A. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives The objective of this study is to compare the visibility and size of Dorello's canal (DC) on magnetic resonance imaging between patients with idiopathic intracranial hypertension (IIH) and control patients, for its evaluation as a potential novel marker for chronic increased intracranial pressure (ICP).Design Retrospective blinded case–control study.Setting Tertiary care academic center.Participants Fourteen patients with spontaneous cerebrospinal fluid (CSF) rhinorrhea and diagnosed IIH, as well as an equal number of age and gender-matched controls.Main Outcome Measures Radiographic presence or absence of visible CSF sleeve within DC as well as CSF sleeve width when present.Results Following review of 28 IIH canals and 28 control canals, IIH patients were significantly more likely to have a visible CSF sleeve within DC and to have a wider measured medial entrance to DC (p < 0.001).Conclusion Identification of CSF evagination into DC may serve as a reliable marker for increased ICP in the IIH population. This finding should be considered in the future as paradigms for diagnosis of IIH continue to evolve.
Keywords: Gruber's; IIH; benign intracranial; pseudotumor; empty sella; skull base; MRI; radiologic; radiographic